2016
DOI: 10.1111/jir.12335
|View full text |Cite
|
Sign up to set email alerts
|

Attentional bias in problematic drinkers with and without mild to borderline intellectual disability

Abstract: Taking the large variability in the strength of the attentional bias and the poor psychometric qualities of the measures into consideration, it is concluded that the use of these measures for clinical purposes is discouraged.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 49 publications
0
9
1
Order By: Relevance
“…This result showed that, although they have the will to control the attentional bias to addiction-related cues after the withdrawal training, they still cannot control the automatic processing advantage to addiction-related cues. Subsequent studies of eye movements, such as alcohol addicts on alcohol-related cues 47 , 48 , obesities on food-related cues 49 , 50 , gambling addicts on gambling-related cues 51 , and heroin addicts on heroin-related cue 52 , have reached similar conclusions. These studies have suggested that addicts may have an unconscious automatic attentional processing advantage to addictive cues.…”
Section: Discussionmentioning
confidence: 75%
“…This result showed that, although they have the will to control the attentional bias to addiction-related cues after the withdrawal training, they still cannot control the automatic processing advantage to addiction-related cues. Subsequent studies of eye movements, such as alcohol addicts on alcohol-related cues 47 , 48 , obesities on food-related cues 49 , 50 , gambling addicts on gambling-related cues 51 , and heroin addicts on heroin-related cue 52 , have reached similar conclusions. These studies have suggested that addicts may have an unconscious automatic attentional processing advantage to addictive cues.…”
Section: Discussionmentioning
confidence: 75%
“…One eye-tracking study (Hobson et al, 2013) has even suggested that craving intensity is a stronger determinant of attentional bias than the level of alcohol consumption in regular drinkers. Nevertheless, these associations have not been supported by more recent studies (Van Duijvenbode et al, 2017; Wilcockson et al, 2019) and thus need further investigation.…”
Section: Introductionmentioning
confidence: 65%
“…The association between AB and craving might therefore be a specific characteristic of problematic alcohol use, and less related to social drinking. However, given that recent studies in clinical samples also failed to find an association between AB and craving [12,39], it might also be that insufficient internal consistency and test-retest reliability of AB tasks limited their capacity to appropriately capture AB, making it difficult to find the proposed relation with craving.…”
Section: Discussionmentioning
confidence: 99%
“…However, although eyetracking can measure overt attention shifts (responding by directly moving and focussing the gaze on a target), it does not measure covert attention shifts (responding by seeing something peripherally without directly focussing the gaze on a target). Eye-tracking might be a valuable addition to this field of research, but as also encouraged by other researchers [12] a task that can reliably measure the influence of covert attention shifts remains also desirable (see for example attempts to improve the reliability of the visual probe task, [13]).…”
Section: Introductionmentioning
confidence: 99%